Characterization of the complete chloroplast genome of Salvia hispanica (Lamiaceae). Issue 2 (2nd April 2020) - Zhang, Xue-Jie; Chen, Cui; Wang, Rong; Yao, Yan; Liu, Ling-Xiao; Zhang, Luo-Yan
Abstract: Salvia hispanica is an annual food and oil crop native to Mexico and Guatemala. In this study, we report the complete chloroplast genome (plastome) of S. hispanica . The plastome was 150, 980 bp in length and comprises a large single-copy region (82, 274 bp), a small single-copy region (17, 534 bp), and a pair of inverted repeats (25, 586 bp). It encodes 114 unique genes, including 80 protein-coding genes (PCGs), 30 tRNAs, and 4 rRNAs. The overall GC content of this plastome was 38.0%. Phylogenomic analysis of all PCGs revealed that S. hispanica was closely related to S. bulleyana .